A Pilot RCT of an Internet Intervention to Reduce the Risk of Alcohol-Exposed Pregnancy - Ingersoll, Karen (Alcohol Clin Exp Res, 2018)
BACKGROUND: Preventing alcohol-exposed pregnancies (AEP) could reduce the incidence of Fetal Alcohol Spectrum Disorders. Previous face-to-face interventions significantly reduced risk for AEP, but a scalable intervention is needed to reach more women at risk. METHODS: This study compared a 6 Core automated, interactive, and tailored Internet intervention, the Contraception and Alcohol Risk Reduction Internet Intervention (CARRII), to a static patient education (PE) website for its effect on alcohol-exposed pregnancy risk. Participants were recruited online to a pilot randomized clinical trial with baseline, 9 weeks post-treatment, and 6 month (6M) follow-up assessments. 71 women completed online questionnaires and telephone interviews and were randomized to CARRII (n=36) or PE (n=35). Primary outcomes were rates of risky drinking, unprotected sex episodes, and AEP risk, collected from online prospective diaries. RESULTS: CARRII participants showed significant reductions in rate of unprotected sex from pre-treatment (88.9%) to post-treatment (70.6%) (p<.04), and to 6M follow-up (51.5%), (p<.001); rate of risky drinking from pre-treatment (75.0%) to post-treatment (50.0%) (p<.02), but insignificant change from pre-treatment to 6M follow-up (57.6%) (p<.09); and rate of AEP risk from pre-treatment (66.7%) to post-treatment (32.4%) (p<.001) and to 6M follow-up (30.3%) (p<.005). PE participants demonstrated no significant changes on all three variables across all time points. Intent-to-treat Group by Time tests were not significant, but power was limited by missing diaries. Over 72% of CARRII participants completed all 6 Cores. Exploratory analyses suggest that higher program utilization is related to change. CONCLUSIONS: These data show that CARRII was acceptable, feasible, promising to reduce AEP risk, and merits further testing in a fully powered RCT.